EFFECT OF SARPOGRELATE ON FISTULA PATENCY OF FOREARM ARTERIOVENOUS ANASTOMISIS IN UREMIC PATIENTS - Jun Yuto; Yosuke Ehara; Kazuhiko Shibata; Tamio Iwamoto; Gen Yasuda; Keisuke Yatsu; Mari Katsumata; Nobuhito Hirawa (The Korean Society of Nephrology, 2012)
Subcutaneous arteriovenous fistula in the forearm is a common vascular access for hemodialysis. However, primary failure of native fistula occurs because of either thrombosis formation within the first several weeks after surgery or immature vein dilatation. To evaluate the effect of platelet inhibition on fistula thrombosis and maturation failure, we used an antiplatelet agent, sarpogrelate hydrochloride, in our study. The study was designed as an open-label, parallel, prospective, randomized study for 8 weeks, comparing patients receiving sarpogrelate 300 mg/day (sarpogrelate group, n=33) with controls receiving no medication (n=46). The primary outcome was fistula patency failure determined by pulse Doppler ultrasound examination of the arteriovenous fistula performed 8 weeks after surgery. Pulse wave velocity was also measured to determine the ankle brachial pressure index (ABI). The drug was well-tolerated and did not increase bleeding events during the 8-week study period. In the sarpogrelate group, patency failure occurred in 1 of 33 patients (3.0%), and the occlusion rate was significantly lower (P=0.001) than that in the control group (3 of 46 patients; 6.5%). Average blood flow rate in the sarpogrelate group was 546±174 mL/min, and was significantly higher (P=0.036) than 448±183 mL/min in the control group. However, the diameter of the shunt vessel in the sarpogrelate group was 5.2±1.3 mm, which was not different from 5.1±0.6 mm in the control group. The Vmax was not significantly different between two groups (1.01±0.56 m/sec in the sarpogrelate group and 0.89±0.66 m/sec in the control group). In all patients (n=79), blood flow correlated with ABI (r=0.34, P=0.045). Our results suggest that sarpogrelate reduces the frequency of fistula patency failure. Sarpogrelate may maintain fistula patency, which is necessary for hemodialysis, by increasing ABI.